MANAJEMEN RISIKO, FUNGSI DAN MEKANISMENYA - Harimurti, Fadjar (Universitas Slamet Riyadi, 2006)
Abstract In general we out for to always obviate all uncertainty element, as long as can be conducted. Existence of uncertainty element cause us always pay attention things related to uncertainty of itself. We possible try identification, risk type which is possible faced and how to obviate or manage risk in a state of is satisfying. Risk by many expert interpreted from the aspect of different approach, depended from its importance. But that way for the purpose of this study, risk defined by as an uncertainty to the happening. In statistical language of risk measured from deviation variance to the what expected (value expected). This uncertainty element oftentimes generates a loss and or damage. This matter represent the nature of universal, almost always is on all human life aspect. Keywords: Risk management, uncertainty.